Obesity as a risk factor for cardiovascular disease: focus on ultrasound - D. A. Tsygankov; O. M. Polikutina (Российский кардиологический журнал, 2021)
For many decades, obesity has been one of the main risk factors for cardiovascular disease. Despite medical advances, the obesity increases contribution to morbidity and mortality from cardiovascular diseases. Numerous anthropometric criteria for obesity are well-studied, simple and inexpensive tools for diagnosing overweight in the population. However, their accuracy is comparatively low. In particular, it is impossible to determine body composition based on these criteria, which is a key point in cardiovascular risk stratification. Despite the relatively short period of ultrasound practice for obesity diagnosis, convincing evidence has already been obtained of their high accuracy and effectiveness in predicting the risk of cardiovascular disease. Given the continuous improvement of ultrasound equipment, the studied criteria should be implemented in routine clinical and research practice. This literature review describes the central parameters used in the ultrasound diagnosis of obesity, their contribution to both conventional risk factors and cardiovascular diseases itself.